Europe’s Port Achilles’ Heel - Paché, Gilles A. (Technium Social Sciences Journal, 2026)
For several years, the growing vulnerabilities of European ports have become increasingly evident, revealing how exposed critical infrastructures are to simultaneous cyber, geopolitical, and organizational risks. The rapid digitization of port operations, coupled with the deep interconnection of global supply chains, has heightened the dependence of freight flows on complex IT systems, in which even minor failures can trigger major disruptions. As a result, ports are becoming high-value targets for actors seeking either to destabilize commercial activity or exploit structural weaknesses. This research note highlights the convergence of several issues: extreme process optimization that undermines system resilience, increasing reliance on heterogeneous technologies, and persistent difficulties in coordinating multiple public and private stakeholders. At the same time, the European Union (EU) faces strategic constraints due to the absence of a unified logistical vision and stark disparities in modernization between major gateways and secondary ports. In response, four priority areas of action emerge: integrating logistical policy into the broader EU industrial strategy, accelerating the digital transformation of port infrastructure, reinforcing cybersecurity and civil-military cooperation mechanisms, and harmonizing operational standards to enhance the overall resilience of the European port system.